2020
DOI: 10.1101/2020.04.11.20061739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Efficacy of Intravenous Immunoglobulin Therapy in Critical Patients with COVID-19: A Multicenter Retrospective Cohort Study

Abstract: ≤ 7 days) of IVIG with high dose (> 15 g/d) improves the prognosis of critical type patients with COVID-19. Meaning:This study provides important information on clinical application of IVIG in treatment of SARS-CoV-2 infection, including patient selection, administration timing and dosage. AbstractImportance: Coronavirus disease 2019 (COVID-19) has become pandemic, causing more than 1.5 million infections and over ten-thousands of deaths in a short period of time worldwide.However, little is known about its pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…The IVIG was administered to 174 cases out of 325 patients. The obtained results indicated a lower lymphocyte count and oxygenation index, as well as higher levels of IL-6 plasma and lactate, in the IVIG group than in the other group (27). Likewise, in the present study, the lymphocyte count decreased following IVIG therapy.…”
Section: Discussionsupporting
confidence: 77%
“…The IVIG was administered to 174 cases out of 325 patients. The obtained results indicated a lower lymphocyte count and oxygenation index, as well as higher levels of IL-6 plasma and lactate, in the IVIG group than in the other group (27). Likewise, in the present study, the lymphocyte count decreased following IVIG therapy.…”
Section: Discussionsupporting
confidence: 77%
“…After adjusting the outcomes of the two groups based on the severity of illness, however, results demonstrated that administration of IVIg did significantly decrease 60-day mortality rates. The same study also showed that both IVIg dosage (> 15 g/d) and administration period (≤ 7 days after hospital admission) could improve efficacy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects on mortality and outcomes can be generalized to IVIG and vitamin C in our study. IVIG not only did not show the survival benefits in a multicenter retrospective study but also increased total duration of the symptoms and hospital stay [27].…”
Section: Discussionmentioning
confidence: 85%